The F word how we learned to swear by feminism - Caro, Jane.; Fox, Catherine (Catherine Louise); ebrary, Inc. (Sydney, N.S.W. : University of New South Wales Press, 2008)
This book is about the work/life balance and the conflicting messages women receive about how they are supposed to live. It is also about the state of feminism as a concept today feminism has become a dirty word, and the term feminist is now often used to insult and belittle women. The authors describe the ways in which, despite the feminist and sexual revolutions, women are still covertly marginalised the work environment is structured for male bodies, with no default arrangement in place to support pregnancy or motherhood (or fatherhood) in the workplace. Flexible work hours are still considered to be special circumstances, rather than the norm. Furthermore, women are still bearing the burden of housework, raising children and family work. The authors address these issues in a light-hearted, amusing yet no-nonsense manner. The tone is extremely positive, even when the content arouses fury and frustration at the ridiculous inequity taking place under our noses every day. In fact the book deals with a whole lot of f words apart from feminismfriendship, family, fathers, fun and freaking out about how much pressure we put on ourselves to be perfect.
Includes index.
Bibliography: p. 242-243.
Electronic reproduction.
Keywords: Feminism; Quality of work life; Sex discrimination against women; Work and family; Male domination (Social structure); Electronic books